Pengaruh Jarak Buangan Air Limbah Industri di Daerah Jaten-Karanganyar terhadap Kadar Chromium dalam Air dan Tanah Permukaan Saluran Air Pungkuk - Dwi Priyo Ariyanto; Indrowuryanto Indrowuryanto; Hery Widijanto (Caraka Tani: Journal of Sustainable Agriculture, 2005)
The purpose of this research was to know the effect of industry waste water distance in Jaten-Karanganyar on Cr concentration in the water and soils at Pungkuk waterworks, also to know Cr concentration on that waterworks. The kind of this research was explorative research. The independent variable was treatment of take some water and soils sample at 0 km, 0.5 km and 1 km distance from pollutant source at Pungkuk waterworks and control.The result showed that distance where farther can affect Cr6+ concentration change in the soils and in the water were increase. The increasing of Cr6+ concentration change in the soils affected Cr6+ acumulation in the soils. The concentration of Cr6+ in the water has been influenced by value of water pH and EMC. Value of water pH also was influenced water EMC value. From sample analysis result showed that there was not polluted of heavy metal especially Cr6+ (between 0.017-0.093 ppm).